HUBUNGAN PENGETAHUAN IBU TENTANG MANFAAT BERMAIN DENGAN PERKEMBANGAN ANAK PRASEKOLAH DI RA MAMBAUL ULUM GEDUNG KARYA JITU LAMPUNG - Sekar Ningrum, Allania Hanung Putri; Aji Pamungkas, Atik Mahmudah; Paramita, Neni (Jurnal Kebidanan, 2024)
In 2019 it was around 23.1%. Early childhood children in Indonesia suffer from developmental deviations such as deviations in gross motor skills, fine motor skills, and mental emotional deviations. The aim of the research is to determine the relationship between mothers' knowledge about the benefits of play and the development of preschool-age children at RA Mambaul Ulum Gedung Karya Jitu 2023. The design of this research is a descriptive method, with a population & sample of 36 people and using purposive sampling techniques. Data analysis used the chi square test. Based on research results, 19 respondents (100%) had good knowledge about the benefits of play for children (52.8%). The highest number of children's developmental status was doubtful development status as many as 19 children (52.8%). The results of statistical tests using chi square obtained a p-value = 0.018 < 0.005, which means that there is a relationship between mother's knowledge about the benefits of play and the development of preschool children at RA Mambaul Ulum Gedung Karya Jitu 2023. Advice to parents is that they hope to pay attention to play therapy which can help improve and child development, by providing good stimulus by providing play.Keywords: Benefits of play, knowledge, child development